Excessive sleep need following traumatic brain injury: a case–control study of 36 patients. (9th July 2013) - Sommerauer, Michael; Valko, Philipp O.; Werth, Esther; Baumann, Christian R.
Summary Increased sleep need following traumatic brain injury, referred to in this study as post‐traumatic pleiosomnia, is common, but so far its clinical impact and therapeutic implications have not been characterized. We present a case–control study of 36 patients with post‐traumatic pleiosomnia, defined by an increased sleep need of at least 2 h per 24 h after traumatic brain injury, compared to 36 controls. We assessed detailed history, sleep‐activity patterns with sleep logs and actigraphy, nocturnal sleep with polysomnography and daytime sleep propensity with multiple sleep latency tests. Actigraphy recordings revealed that traumatic brain injury (TBI) patients had longer estimated sleep durations than controls (10.8 h per 24 h, compared to 7.3 h). When using sleep logs, TBI patients underestimated their sleep need. During nocturnal sleep, patients had higher amounts of slow‐wave sleep than controls (20 versus 13.8%). Multiple sleep latency tests revealed excessive daytime sleepiness in 15 patients (42%), and 10 of them had signs of chronic sleep deprivation. We conclude that post‐traumatic pleiosomnia may be even more frequent than reported previously, because affected patients often underestimate their actual sleep need. Furthermore, these patients exhibit an increase in slow‐wave sleep which may reflect recovery mechanisms, intrinsic consequences of diffuse brain damage or relative sleep deprivation.